An innovative biosensing approach for Aflatoxin B1 detection via electrical impedance measurement - Ustunsoy, Recep; Ertas, Tahsin; Gultekin, Hulya Eraslan; Ergenc, Ali Fuat; Dinc, Bircan; Bektas, Muhammet (ELSEVIER, 2025)
Aflatoxin B1 (AFB1) contamination poses a significant threat to food safety and public health, creating an urgent need for reliable and effective detection methods. This study presents a fast and sensitive biosensor for detecting AFB1 in complex food samples. Scanning Electron Microscopy (SEM) shows the current functionalization of tungsten wires with antibodies and multi-walled carbon nanotubes (MWCNTs). The surface morphological changes are easily visible as they give rise to a roughened, textured surface that provides a greater active area, since the surface used for hydrogen evolution. Results from Differential Scanning Calorimetry (DSC) show that the enthalpy changes associated with antibody AFB1 interactions are greater at higher AFB1 concentrations, indicative of higher affinities of binding interactions. Differential scanning calorimetry (DSC) thermograms display clear endothermic peaks corresponding to different levels of AFB1, providing information about the melting point as well as the stability and binding characteristics of the antibody complex. The biosensor achieves a broad detection range (0.1 ppb to 30 ppb), with charge transfer resistance decreasing from 1.5 ohm & sdot;cm2 to 0.5 ohm & sdot;cm2 as AFB1 concentration increases. Using Electrical Impedance Spectroscopy (EIS) and advanced nano- materials, this biosensor enables real-time monitoring of molecular interactions. By addressing the limitations of traditional detection methods, it offers a practical solution for enhancing food safety and preventing AFB1 contamination.
Keywords: Biosensor; Electrical impedance spectroscopy (EIS); Scanning electron microscopy (SEM); Differential scanning calorimetry (DSC); Aflatoxin B1 (AFB1); ANTIBODY IMMOBILIZATION; B-1; Food Science & Technology